Commentary on Early Identification and Intervention for Students With Mathematics Difficulties - Pedrotty Bryant, Diane (Journal of learning disabilities, 2005)
Bryant reflects on the key highlights of Gersten et al's article by connecting their information to other relevant sources and findings related to the nature of mathematics difficulties (MD), early mathematics instruction, and differentiating instruction for struggling students. Among other things, she notes that Gersten et al provide an excellent summary of the highlights of key findings in the area of MD, number sense, and instruction. The findings presented in the Gersten et al article provide a sense of optimism that the area of early mathematics and struggling students is gaining national attention as an area in need of research.